The methodology of surveillance for antimicrobial resistance and healthcare-associated infections in Europe (SUSPIRE): a systematic review of publicly available information. (February 2018) - Núñez-Núñez, M.; Navarro, M.D.; Palomo, V.; Rajendran, N.B.; del Toro, M.D.; Voss, A.; Sharland, M.; Sifakis, F.; Tacconelli, E.; Rodríguez-Baño, J.; ,
Abstract: Objectives: Surveillance is a key component of any control strategy for healthcare-associated infections (HAIs) and antimicrobial resistance (AMR), and public availability of methodologic aspects is crucial for the interpretation of the data. We sought to systematically review publicly available information for HAIs and/or AMR surveillance systems organized by public institutions or scientific societies in European countries. Methods: A systematic review of scientific and grey literature following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines was performed. Information on HAIs and/or AMR surveillance systems published until 31 October 2016 were included. Results: A total of 112 surveillance systems were detected; 56 from 20 countries were finally included. Most exclusions were due to lack of publicly available information. Regarding AMR, the most frequent indicator was the proportion of resistant isolates (27 of 34 providing information, 79.42%); only 18 (52.9%) included incidence rates; the data were only laboratory based in 33 (78.5%) of the 42 providing this information. Regarding HAIs in intensive care units, all 22 of the systems providing data included central line–associated bloodstream infections, and 19 (86.3%) included ventilator-associated pneumonia and catheter-associated urinary tract infections; incidence density was the most frequent indicator. Regarding surgical site infections, the most frequent procedures included were hip prosthesis, colon surgery and caesarean section (21/22, 95.5%). Conclusions: Publicly available information about the methods and indicators of the surveillance system is frequently lacking. Despite the efforts of European Centre for Disease Control and Prevention (ECDC) and other organizations, wide heterogeneity in procedures and indicators still exists.